ANALISIS KERUSAKAN UJUNG AS T-LINK CONVEYOR TERMINAL KEDATANGAN DI BANDAR UDARA SULTAN HASANUDDIN MAKASSAR - Kurniawanto, Hari; Inten Suwono, Niedya; Tangkas Bramanto, Halim; Alkholif, Muhammad Qomarudin; Nabila Putri, Dea; Tri Saputra, Akbar Reza (Jurnal Teknik Mekanikal Bandar Udara, 2023)
This research aims to improve the safety and comfort of BaggageHandling System (BHS) users, especially at the domestic arrival terminalin order to facilitate flights at Sultan Hasanuddin International Airport,through improving and optimizing the performance of the BHS, especiallyAs T-Link section to connect the T-Link and the arrival pallet conveyor.For damage to the end of the T-Link As, it can be handled by changingparts. The cause of the tip of As T-Link is damaged after observationaldata collection, there are a number of disassembly that are not inaccordance with the SOP for disassembling the As T-Link roller bearing,one of which is by using a hammer. Thus, so that this problem does notoccur again, it is necessary to add additional applicable SOPs, one ofwhich is the use of trekkels in disassembling roller bearings, providing WD when disassembling roller bearings, and applying grease after installing rollerbearings